Product Life Cycle Opportunities for Digital and Sustainable Transformation - Petrillo, Antonella; De Felice, Fabio (IntechOpen, 2021)
Globalization and increased competition are forcing companies to review and improve their production processes to be more sustainable. However, a clear vision and environmental culture are lacking because, even today, companies are motivated to act to improve the environment essentially by compliance with government regulations and the opportunity to achieve profit growth. This book presents practices, challenges, and opportunities for the digital and sustainable transformation of business as we know it.